18. ASSESSMENT THE EFFECT OF FOOT SOAK “TIEU DUONG TUC XI KHANG” IN COMBINATION WITH HYDROACUPUNCTURE IN THE TREATMENT OF COMPLICATIONS OF PERIPHERAL NERVES OF THE LOWER EXTREMITIES IN PATIENTS WITH TYPE 2 DIABETES (Vietnam Journal of Community Medicine, 2023)
Background: Complications of diabetes are very diverse, with peripheral neuropathy of the lower extremities accounting for a very high rate. Modern medicine still has difficulties treating this pathology. Combining treatment with modern medicine and traditional medicine with the desire to improve clinical efficiency and improve the quality of life for patients is necessary, but studies are needed to prove its effectiveness the actual result of the combined method. Objectives: Evaluating the effect of foot bath “Tieu Duong tuc xi Khang” with Methylcobal hydrotherapy to treat peripheral nerve complications of the lower extremities in patients with type 2 diabetes. Subjects and methods: Clinical intervention compared before, after treatment, and control in 60 patients with peripheral neuropathy of the lower extremities due to type 2 diabetes equally divided into 2 groups. The study group used the foot bath “Tieu Duong tuc xi Khang” combined with hydro-acupuncture, and the control group used hydro-acupuncture Methylcobal clinical assessment criteria according to the VAS, UKST, SF-36 scale and some biochemical blood indices. The study period was 20 days at Danang Traditional Medicine Hospital from June 2022 to December 2022. Results: The study group improved the functional and physical symptoms better than the control group (p
Keywords: Tieu duong tuc xi khang, lower extremity peripheral neuropathy.